Health and Nutrition in Urban Bangladesh : Social Determinants and Health Sector Governance - Govindaraj, Ramesh (Washington, DC: World Bank, 2017)
Urbanization is occurring at a rapid pace in Bangladesh, accompanied by the proliferation of slum settlements, whose residents have special health needs given the adverse social, economic, and public environmental conditions they face. Over the past 45 years, the country’s health and nutrition policies and programs have focused largely on rural health services. Consequently, equitable access of urban populations—particularly the urban poor—to quality health and nutrition services has emerged as a major development issue. However, the knowledge base on urban health and nutrition in Bangladesh remains weak.